The Illegal Network of Foreign Workers: The Missing Indonesian Migrant Workers in Japan - Beby Fitri Xaviera Gunawan; Kurniawaty Iskandar (Budapest International Research and Critics University, 2022)
Migrant workers in Japan is partially an act of runaway and escaping done by the migrant workers. This action is carried out by migrant workers who are mostly trainees. This research explains the role of the illegal network as a tool used by the workers in order to help them run away from the company they work for. Massey’s perspective of migration network theory is used to analyze the illegal activities shown by the migrant community. The reason behind their decision in choosing the illegal action is identified using the theory of rational choice. The data were collected by applying the literature study and analyzed using the descriptive qualitative method. The result shows that the illegal network of migrant workers had successfully broadened the community of the migrant workers in Japan because all of the participants are connected by kinship and share the same common interests. The broker is the third party that is involved as a connector between migrant workers and an illegal backer. There are several motives or reasons performed by the workers based on their rational choice which are, deciding to run away from their workplace because of seeking a better opportunity in a new place, expecting a higher salary, and the content feeling to stay in Japan. The impacts caused by this illegal action is not really significant for the next process in sending Indonesian workers to Japan. It is because the migration itself happens under each country’s concerns in dealing with employment issues.